2015
DOI: 10.1016/j.engfracmech.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between disbond growth and the release of strain energy

Abstract: Current prediction methods for growth of disbonds under fatigue loading are generally based on a correlation with either the maximum strain energy release rate (SERR) or the SERR range. This paper highlights some issues with this approach. In particular, it is argued that the maximum SERR or the SERR range alone do not give sufficient information to uniquely characterize the driving force for crack growth. Furthermore it is argued that the relationship between crack growth rate and loss of strain energy should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
(32 reference statements)
2
26
0
Order By: Relevance
“…Recently, studies on fatigue delamination growth in composite laminates and adhesively bonded structures have been reported that evaluate the phenomena using energy principles [12][13][14][15]. In these studies, the concept of the energy dissipation rate dU/dN is correlated to the fatigue crack growth rate da/dN.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on fatigue delamination growth in composite laminates and adhesively bonded structures have been reported that evaluate the phenomena using energy principles [12][13][14][15]. In these studies, the concept of the energy dissipation rate dU/dN is correlated to the fatigue crack growth rate da/dN.…”
Section: Introductionmentioning
confidence: 99%
“…(1), where b is the width of the specimen. It is notable that this procedure is based on an energy balance, and it accounts for the stress ratio in its definition, often collapsing fatigue curves for different stress ratios [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the case stiffeners are bonded to the FML panel, the phenomenon is commonly referred to as adhesive disbonding or disbond growth rather than delamination. [19][20][21] In the case stiffeners are riveted to the FML panel, then the K stiffeners term can be evaluated through a methodology originally proposed by Vlieger 22,23 and later adapted by others. 24,25 3 | SUPERIMPOSING MATERIALS SUPERIMPOSES CRITICISM AND PREJUDICE What has become evident in the development of FMLs for aeronautical applications is that the combination of two distinctively different materials into a single structural material concept invites two communities to express concerns and criticism.…”
Section: Superimposing Layers Requires Superposition Principlesmentioning
confidence: 99%